Latinidade: uma questão de identidade em manuais didáticos de língua portuguesa - Santos, Clemilton Pereira dos (2017)
Our research aims at making some considerations on the Latin cultural identity as it was conducted in the Portuguese language teaching material named Português I, by Domício Proença Filho and Maria Helena Duarte Marques, published by Editora Liceu in 1968 and adopted during the Brazilian military regimen after and because of the Mec/USAID agreements signed in 1965 by the Brazilian Government and the Agency for International Development (AID). This teaching material will be studied in parallel and in opposition to another one, Texto e Contexto, composed by Lidio Tesoto and Norma Discini (responsible for the production of the texts in the book). The latter was published by Editora do Brasil in the 80’s, the exact summit of globalization. Our purpose is to set a parallel bettwen both books so as to make it possible to check what cultural aspects are spread through the teaching materials and in what way they helped to build up the collective cultural imaginary of latinity in Brazil. By means of this study we intend to defend the idea that changes from our Latin-European origin to a Latin-American origin, due to colonialism processes and coloniality-modernity processes afterwards, are responsible to determine our cultural identity, which is nowadays more American than Latin, concerning customs and knowledges of our cultural roots, which are so indispensable to our formation both as human beings and citizens in times of globalized identities. of domination and submission as colonies of being and knowing brings about what Mignolo has called colonial wound (herida colonial) and this leads us to believe in our defficient identitary formation: “el sentimento de inferioridad impuesto em los seres humanos que no encajam em el modelo predeterminado por los relatos euro-americanos.” (MIGNOLO, 2005:17). Confronted with this context, we ask: How are Latin American cultural identity reproduced and represented through discourse of the discursive genre textbook? We are aware that every society receives new features and characteristics, but they don´t put their traditions aside; on the contrary, these traditions may be transformed and upgraded according to the needs and daily uses of that same society. However, how do these updates tend to identify us culturally, as citizens of the 21st century, through the base-texts of textbooks in the Collective Cultural Imaginary of our children? For the development of this study, our theoretical foundation will rely on studies by Elia (1957;1966), Nóbrega (1962), Coutinho (1973), Faria (1941), Romanelli (1986), Althusser (1998), Giddens (1991), Burke (1995), Canclini (1999), Grimal (1999), Bassetto (2001), Hall (2005), Mignolo (2005), Bauman (2008), Neves(2006), Orecchioni (1997), Bakhtin (1997a), (1997b), Marcuschi (2008), Cattelan(2009), among others who, in the course of their work, ground discussions about issues concerning the ideological function of textbooks in Brazil, coloniality / modernity and discursive construction of cultural identity “dispensable” in history and teaching of language and Latin culture in Portuguese language, as well as the role of adjectives, adjective clauses and discursive genres (compositional structure and thematic contents) as discursive modalizers and formers of a subaltern Latin cultural identity, in portuguese language teaching manuals in Brazil.